National surveillance of disseminated gonococcal infection: preliminary findings from cross-sectional survey data in England, 2016–21. (November 2021) - Merrick, Rachel; Pitt, Rachel; Enayat, Qudsia; Day, Michaela; Thorn, Louise; Mohammed, Hamish; Sinka, Katy; Cole, Michelle; Fifer, Helen
Abstract: Background: Disseminated gonococcal infection (DGI) is caused by the spread of Neisseria gonorrhoeae into the bloodstream and can lead to severe illness. We established a surveillance system for DGI in England to quantify the burden of disease. Methods: On June 26, 2020, all sexual health clinicians in England were asked to retrospectively and prospectively report DGI cases to Public Health England. Case finding was conducted for N gonorrhoeae isolates confirmed by the national reference laboratory from sterile sites from June, 2019 onwards. A secure web-based survey was shared with clinicians to collect demographic and clinical data on affected individuals. Individuals with culture-positive or 16S rDNA-positive N gonorrhoeae at a sterile site were classified as confirmed cases. Probable cases were defined as individuals with culture-positive or nucleic acid amplification test-positive N gonorrhoeae from a non-sterile site with clinical manifestations of DGI. Findings: Between June 26, 2020, and June 1, 2021, 11 cases of DGI (seven confirmed, four probable) were reported. Cases were diagnosed in 2016 (n=1), 2017 (n=1), 2018 (n=2), 2019 (n=6) and 2020 (n=1). Among the confirmed cases, N gonorrhoeae was identified in joint or synovial fluid in six (86%). Ten (91%) of 11 were among men, seven of whom identified as men who have sex with men or bisexual. The median age of those affected was 27 years (IQR 25–43) and three (27%) of eleven were living with HIV. Nine (82%) of 11 patients were hospitalised, for a median of 8 days (IQR 3–15), and tenosynovitis (six cases, 55%) and polyarthralgia (five cases, 46%) were the most common symptoms. Interpretation: Historically, DGI is estimated to occur in 0·5–3·0% of individuals with untreated gonorrhoea. With 70 936 gonorrhoea diagnoses reported nationally in 2019, our data likely underestimate prevalence. Awareness of the ongoing need to report DGI to Public Health England should be promoted to clinicians, including those working in non-sexual health settings due to the variety of clinical presentations. Funding: None.